Arterial stiffness mediates the effect of salt intake on systolic blood pressure. Issue 11 (7th October 2018) - Siriopol, Dimitrie; Covic, Adrian; Iliescu, Radu; Kanbay, Mehmet; Tautu, Oana; Radulescu, Luminita; Mitu, Ovidiu; Salaru, Delia; Dorobantu, Maria
Abstract : Accumulating evidence indicates that higher levels of salt intake are associated with higher blood pressure levels. The aim of our analysis was to test the hypothesis that the effect of urinary sodium excretion (UNaV) on systolic blood pressure (SBP) is mediated through estimated glomerular filtration rate (eGFR) and arterial stiffness and also to test the direction of the relationship between eGFR and arterial stiffness, in both hypertensive and normotensive patients. We assessed the potential for connection between UNaV and SBP and mediators (eGFR and pulse wave velocity [PWV]) of this relationship using structural equation models of data from 1599 adults ≥18 years of age and without chronic kidney disease who participated in the Third Epidemiologic Study concerning the Prevalence of Arterial Hypertension and Cardiovascular Risk in Romania (SEPHAR III). In hypertensive patients, the indirect effect, mediated through PWV, of UNaV on SBP was 23.9% and 27.7% of the total effect of UNaV on SBP, while in normotensive patients the contribution of PWV to the total effect of UNaV on SBP was slightly lower (15.9% and 18.3% of the total effect of UNaV on SBP). Taken together, our findings support the conclusion that UNaV influences SBP, both directly and indirectly, through the effect on PWV.